Perbandingan Hasil Belajar Siswa Menggunakan Metode Problem Solving Dengan Metode Ceramah Pada Mata Pelajaran Fiqih Di MTs PN 4 Medan - Santika, Dilla; Hasbi, Syaukani (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
Student learning outcomes are given to the results of student school assignments that are difficult to learn. The level of student learning outcomes can be influenced by many factors, including international factors (originating from within the students themselves) and external factors (originating from outside the students' self). Quality and relevant learning cannot happen by itself; it must be added. For those who are building meaning or understanding something, learning is a vital activity for them, so it is necessary to provide support for those who are building ideas. A good learning method is one that is intended to teach students. The education system recognizes students as learning subjects. Another term is